FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI WAJIB PAJAK ORANG PRIBADI ATAS PERILAKU PENGGELAPAN PAJAK (Studi Empiris pada Wajib Pajak Terdaftar di KPP Pratama Semarang Candisari) - Wahyu Rachmadi; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2014)
This study aimed to analyze factors that affect taxpayer’s perceptions on tax evasion. These factors are the taxpayer’s knowledge, service of tax officer and tax sanction. The population in this study are individual taxpayers who registered in KPP Pratama Semarang Candisari. This research was replicated from the previous research, Prasetyo (2010) and Rahman (2013). The difference between this research and the previous ones are in the object and the location. Previous studies were done at Surakarta and Jakarta, while this study was conducted with using respondents from individual taxpayer who enrolled at Semarang.The sampling technique in this study used convenience sampling method. Determination of the sample numbers used the formula of Slovin 100 respondents. The hypothesis of this study was analyzed by SPSS software. Then the multiple regression analysis was used to examine the relationship between the variables above. The result of this study indicate that all of hypothesis that have been proposed are accepted. The implications of this study indicate that tax evasion was viewed as unethical acts. Direktorat Jenderal Pajak needs to regularly hold socialization that tax revenue are importance for the development in order to increase awareness of taxation in Semarang.